Pengembangan Perangkat dengan Model Pembelajaran Advance Organizer untuk Meningkatkan Penguasaan Konsep dan Retensi Fisika Peserta Didik - Syari'atul Fitria; Ahmad Harjono; Gunawan Gunawan; Syahrial Ayub (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2021)
This research aims to determine the feasibility of a device with an advance organizer learning model to improve student’s mastery of concepts and physics retention. Learning device developed include syllabus, lesson plans, student worksheet, concept maps, concept mastery and physics retention test instruments. The research design used is Research and Development (R&D) with the 4D model (define, design, develop & disseminate). This research is limited only to the development stage, namely validation by a validator with supporting data in the form of student responses to the developed device. The results of validation using CVR and CVI show that the device is in the very feasible category. The response results showed an average percentage of 99% with very good category. Thus, it can be concluded that the device developed is very suitable for use in learning physics and is predicted to increase the mastery of concepts and student retention.